TEACHER’S QUESTIONING IN CLASSROOM INTERACTION AT SENIOR HIGH SCHOOL - Gina Febriona and Siti Aisyah Ginting (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
This study was about the teacher’s questioning in classroom interaction. This study was aimed to find out the types of teacher’s question in classroom interaction, and the functions of teacher’s questions in teaching learning process. The research design of this study was descriptive qualitative method.The data of this study was taken from the teacher who taught in tenth grade at SMA Swasta Dharmawangsa Medan in academic year 2017/2018. The data were analyzed by using Blosser (1973). The instruments of collecting data were observation, video recording, field notes and interview. It was found that the types of teacher’s question were close and open question and the dominant type is closed question (52,63%). There were seven functions of teacher question, they were check learners understanding, elicit information, control the classroom, arouse interest and curiosity concerning a topic, focus attention on a particular issue or concept, develop an active approach to learning, stimulate students to ask questions of themselves and others. The various of teacher’s questions are the roles of teacher which expected able to motivate students to learn better and avoid boring impression in the classroom interaction, so that the learning process will be better. From the result can be concludes that the teacher was effective in classroom interaction in teaching reading descriptive text andthe teacher interact with the students by using questions.